Utilization of Museum Cipari Through Field trips for History Learning at SMAN 2 Kuningan - Mauludin, Rizky Ady; Kusmayadi, Yadi; Ratih, Dewi (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
This study highlights the importance of history learning in building local historical awareness and motivating students to appreciate cultural heritage. The field trip method, where students learn directly at historical sites, is an effective strategy. The Cipari Archaeological Museum in Kuningan, a megalithic heritage site, offers valuable opportunities for meaningful, contextual history learning. This research aims to explore the museum’s history, describe its use through field trips for Grade X students at SMAN 2 Kuningan, and analyze student responses. Using a descriptive qualitative method, data were collected via observation, interviews, and documentation involving students, teachers, and museum staff. Results show that field trips increase students’ interest, understanding of local history, and active involvement compared to conventional classroom learning. Students engage more enthusiastically with the material, finding the experience concrete and memorable despite challenges like limited time and logistics. The study recommends that history teachers incorporate museum visits into their curriculum with careful planning and follow-up activities to maximize educational benefits.